Effect of Feeding Balanced Ration on Solids-Not-Fat Content of Milk and Production Performance of Lactating Crossbred Cows - Bhanderi, B.M.; Garg, M.R.; Goswami, Ajay; Shankhpal, Sachin (Indian Journal of Animal Nutrition, 2018)
A study was undertaken to investigate the effect of feeding a balanced ration on the solids-not fat (SNF) content of milk and production performance of crossbred cows (n=70) in Anand district of Gujarat, India. OutÂ  of 115 animals, 70 crossbred cows showed low SNF content. Milk yield, milk fat, SNF and net daily income of milk producers were recorded before and after feeding a balanced ration. Nutritional status of animals indicated that about 76% of the animals were given excess protein and energy in the ration, whereas, ration of 83% ofthe animals was deficit in calcium and phosphorus. On feeding a balanced ration for 8 weeks, there was improvement (P